2018
DOI: 10.5098/hmt.11.12
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Conjugate Heat Transfer in Cavity Filled With Saturated Porous Media

Abstract: The conjugate natural convection heat transfer in a partially heated porous enclosure had been studied numerically. The governing dimensionless equations are solved using finite element method. Classical Darcy model have been used and the considering dimensionless parameters are modified Rayleigh number (10 ≤ Ra ≤ 10 3), finite wall thickness (0.02 ≤ D ≤ 0.5), thermal conductivity ratio (0.1 ≤ Kr ≤ 10), and the aspect ratio (0.5 ≤ A≤ 10). The results are presented in terms of streamlines, isotherms and local a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Also, Al-Farhany and Abdulkadhim [22] shows that when the wall thickness increases, the Nusselt number decreases while it increases when the modified Rayleigh number increases. The conjugate natural convection studied numerically by Abdulkadhim et al [23]. It is found that when the Wall thickness increases, the conduction heat transfer dominated.…”
Section: Heat Transfer Inside Cavity With Porous Mediamentioning
confidence: 99%
“…Also, Al-Farhany and Abdulkadhim [22] shows that when the wall thickness increases, the Nusselt number decreases while it increases when the modified Rayleigh number increases. The conjugate natural convection studied numerically by Abdulkadhim et al [23]. It is found that when the Wall thickness increases, the conduction heat transfer dominated.…”
Section: Heat Transfer Inside Cavity With Porous Mediamentioning
confidence: 99%
“…-At the side walls (left and right) x/L Nu x (Völker et al 44 ) Nu x (Present study Equation (18) (18) where h x is the local heat transfer coefficient, which can be estimated from the relation ( where AR is the aspect ratio of the triangle, which can be given as follows:…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The dimensionless governing Equations (14)(15)(16)(17)(18)(19) are solved numerically utilizing the finite volume scheme with the specified boundary conditions. The SIMPLE algorithm is applied to combine the momentum and continuity equations.…”
Section: Solution Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the Middle-Middle arrangement produces higher values of average Nusselt numbers. Abdulkadhim et al [27] used finite element techniques and concluded that increasing the aspect ratio will decrease the heat transfer rate and increase the fluid flow strength.…”
Section: Introductionmentioning
confidence: 99%